Innovative Human Resource Management in Public Authorities as a Way to Improve the Country’s Sustainable Development - Anastasiya ILYINA (Communications of International Proceedings, 2022)
The improvement of the country’s sustainable development requires the application of an innovative approach to human resource management in public authorities. This approach should include the distribution of powers between the head of the public authority, heads of its structural units and their subordinates in accordance with the strategic, tactical and operational goals. Each public authority and its separate structural units are responsible for regulating a specific industry in the locality and in the whole country, depending on its jurisdiction. In this case, public authorities need to ensure the performance of management functions by qualified personnel in accordance with the development of the Sustainable Development Strategy, the implementation of which should rely on human resources able to achieve strategic goals for the benefit of society. Using the methods of scientific abstraction, system analysis and modeling, it is proposed to determine the role of human resources in the country’s sustainable development, consider the relationship between human resource management in the public and private sectors, and formulate a model of the innovative human resource management system in public authority in the process of the Sustainable Development Strategy implementation. As for this model, it is the application of management methods and tools due to the strategic tasks that will help public authorities to achieve a significant effect in the operational, tactical and, therefore, strategic goals. Here this Strategy should be an improved system of normative provisions regulating public administration, and also economic and social relations in labor teams.
Keywords: Human Resource Management; Human Capital; Innovative Management; Sustainable Development.